Polypill Brings Benefits to Patients with Cardiovascular Disease, Both Improving Medication Adherence and Demonstrating the Concept of Chronotherapy [Letter] - Zhu LL; Zhou Q (Vascular Health and Risk Management, 2023)
Ling-Ling Zhu,1 Quan Zhou2 1Geriatric VIP Ward, Division of Nursing, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, 310009, People’s Republic of China; 2Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang Province, 310009, People’s Republic of ChinaCorrespondence: Quan Zhou, Department of Pharmacy, The 2nd Affiliated Hospital, School of Medicine, Zhejiang University, Zhejiang, 310009, People’s Republic of China, Tel +86-571-8778-4615, Email zhouquan142602@zju.edu.cn